Analysis of in vitro chemoresponse assays in endometrioid endometrial adenocarcinoma: an observational ancillary analysis. Issue 1 (December 2016) - Davidson, Brittany; Foote, Jonathan; Brower, Stacey; Tian, Chunqiao; Havrilesky, Laura; Secord, Angeles
Abstract Background Chemotherapy plays a role in the treatment of endometrioid endometrial cancer (EEC); however, tumor grade may affect response. Our objective was to evaluate associations between tumor grade and in vitro chemoresponse. Methods We conducted an analysis of primary tumor samples from women with EEC undergoing in vitro chemoresponse testing. Results were classified as sensitive (S), intermediate (I), or resistant (R) to each drug tested. Correlations between tumor grade and response were examined. Results Data was collected from 159 patients: 28 with grade 1 (18%), 52 with grade 2 (32%), and 79 (50%) with grade 3 tumors. Median age of patients was 62 (range 31–92). Most patients were Caucasian (83%) with advanced disease (Stage III: 50.9%; Stage IV: 13.2%). Overall chemoresponse was similar across all grades. Fifty percent, 56 and 51% for grade 1, 2, and 3 tumors, respectively, demonstrated S results to at least 1 agent. There was no association between grade and in vitro response to chemotherapy agents (p > 0.05) except a marginal association between grade and doxorubicin response (p = 0.08). Grade 1 and 2 cancers were more likely to demonstrate R results for doxorubicin compared to grade 3 cancers (G1: 19% vs G2: 25% vs G3: 8%;p = 0.08). In a subset tested for all 7 agents, only one patient tumor was pan-R and 4 were pan-S. Conclusions Based on our data, grades 1–3 EEC have similar in vitro chemoresponse. These findings suggest that chemotherapy may be useful in advanced low grade EECs, but further clinical correlation is needed.